Psychosocial interventions for benzodiazepine harmful use, abuse or dependence - Darker, Catherine D; Sweeney, Brion P; Barry, Joe M; Farrell, Michael F; Donnelly-Swift, Erica (Cochrane database of systematic reviews, 2015)
Benzodiazepines (BZDs) have a sedative and hypnotic effect upon people. Short term use can be beneficial but long term BZD use is common, with several risks in addition to the potential for dependence in both opiate and non-opiate dependent patients. To evaluate the effectiveness of psychosocial interventions for treating BZD harmful use, abuse or dependence compared to pharmacological interventions, no intervention, placebo or a different psychosocial intervention on reducing the use of BZDs in opiate dependent and non-opiate dependent groups. We searched the Cochrane Central Register of Controlled Trials (CENTRAL- the Cochrane Library issue 12, 2014) which includes the Cochrane Drugs and Alcohol Group Specialized Register; PubMed (from 1966 to December 2014); EMBASE (from 1988 to December 2014); CINAHL Cumulative Index to Nursing and AlliedHealth Literature (1982 to September 2013); PsychINFO (1872 to December 2014); ERIC (Education Resources Information Centre, (January 1966 to September 2013); All EBM Reviews (1991 to September 2013, Ovid Interface); AMED (Allied & Alternative Medicine) 1985 to September 2013); ASSIA (Applied Social Sciences Index & Abstracts (1960 to September 2013); LILACS (January 1982 to September 2013);Web of Science (1900 to December 2014);Electronic Grey Literature Databases: Dissertation Abstract; Index to Theses. Randomised controlled trials examining the use of a psychosocial intervention to treat BZDs versus pharmacological interventions,no intervention, placebo or a different psychosocial intervention on reducing the use of BZDs in opiate dependent and non-opiate dependent groups. We used the standard methodological procedures outlined in Cochrane Guidelines. Twenty-five studies including 1666 people met the inclusion criteria. The studies tested many different psychosocial interventions including cognitive behavioural therapy (CBT) (some studies with taper, other studies with no taper), motivational interviewing (MI),letters to patients advising them to reduce or quit BZD use, relaxation studies, counselling delivered electronically and advice provided by a general practitioner (GP). Based on the data obtained, we performed two meta-analyses in this Cochrane review: one assessing the effectiveness of CBT plus taper versus taper only (575 participants), and one assessing MI versus treatment as usual (TAU) (80 participants).There was moderate quality of evidence that CBT plus taper was more likely to result in successful discontinuation of BZDs within four weeks post treatment compared to taper only (Risk ratio (RR) 1.40, 95% confidence interval (CI) 1.05 to 1.86; nine trials, 423 participants) and moderate quality of evidence at three month follow-up (RR 1.51, 95% CI 1.15 to 1.98) in favour of CBT (taper)for 575 participants. The effects were less certain at 6, 11, 12, 15 and 24 months follow-up. The effect of CBT on reducing BZDs by> 50% was uncertain for all time points examined due to the low quality evidence. There was very low quality evidence for the effect on drop-outs at any of the time intervals; post-treatment (RR 1.05, 95% CI 0.66 to 1.66), three month follow-up (RR 1.71, 95% CI0.16 to 17.98) and six month follow-up (RR 0.70, 95% CI 0.17 to 2.88).Based on the very low quality of evidence available, the effect of MI versus TAU for all the time intervals is unclear; post treatment(RR 4.43, 95% CI 0.16 to 125.35; two trials, 34 participants), at three month follow-up (RR 3.46, 95% CI 0.53 to 22.45; four trials,80 participants), six month follow-up (RR 0.14, 95% CI 0.01 to 1.89) and 12 month follow-up (RR 1.25, 95% CI 0.63 to 2.47).There was very low quality of evidence to determine the effect of MI on reducing BZDs by > 50% at three month follow-up (RR 1.52,95% CI 0.60 to 3.83) and 12 month follow-up (RR 0.87, 95% CI 0.52 to 1.47). The effects on drop-outs from treatment at any of e time intervals between the two groups were uncertain due to the wide CIs; post-treatment (RR 0.50, 95% CI 0.04 to 7.10), three month follow-up (RR 0.46, 95% CI 0.06 to 3.28), six month follow-up (RR 8.75, 95% CI 0.61 to 124.53) and 12 month follow-up(RR 0.42, 95% CI 0.02 to 7.71).The following interventions reduced BZD use - tailored GP letter versus generic GP letter at 12 month follow-up (RR 1.70, 95%CI 1.07 to 2.70; one trial, 322 participants), standardised interview versus TAU at six month follow-up (RR 13.11, 95% CI 3.25 to 52.83; one trial, 139 participants) and 12 month follow-up (RR 4.97, 95% CI 2.23 to 11.11), and relaxation versus TAU at three month follow-up (RR 2.20, 95% CI 1.23 to 3.94).There was insufficient supporting evidence for the remaining interventions.We performed a 'Risk of bias' assessment on all included studies. We assessed the quality of the evidence as high quality for random sequence generation, attrition bias and reporting bias; moderate quality for allocation concealment, performance bias for objective outcomes, and detection bias for objective outcomes; and low quality for performance bias for subjective outcomes and detection bias for subjective outcomes. Few studies had manualised sessions or independent tests of treatment fidelity; most follow-up periods were less than 12 months.Based on decisions made during the implementation of protocol methods to present a manageable summary of the evidence we did not collect data on quality of life, self-harm or adverse events. CBT plus taper is effective in the short term (three month time period) in reducing BZD use. However, this is not sustained at six months and subsequently. Currently there is insufficient evidence to support the use of MI to reduce BZD use. There is emerging evidence to suggest that a tailored GP letter versus a generic GP letter, a standardised interview versus TAU, and relaxation versus TAU could be effective for BZD reduction. There is currently insufficient evidence for other approaches to reduce BZD use.